Lion & lamb ebook - Patterson, James (2023)
Veena Lion and Cooper Lamb are rival PIs in Philadelphia in this  “fun ride…the romance between Cooper and Veena is artfully handled...endearing characters including Cooper’s two preternaturally clever kids and his Rhodesian ridgeback puppy .”  –Publishers Weekly ​“Great storytelling…a spectacular murder case.” – Kirkus , starred review The city is in a state of shock over the fate of two hometown heroes: Eagles starting quarterback Archie Hughes, and his even more famous wife, Grammy-winning singer Francine Hughes. One spouse is murdered. The other is suspect #1.   Even before the case hits the courtroom, it’s the hottest ticket in town.    For the defense: Cooper Lamb, private investigator to the stars.   For the prosecution: Veena Lion, a sleuth so bright she’s got to wear shades.   Between them, they know every secret in Philadelphia. Together, they prove how two wrongs can make a right. They are Lion & Lamb.